Peningkatan Kemampuan Korps Brimob Polri dalam Bidang KBRN untuk Menghadapi Ancaman Terorisme: Sebuah Pendekatan dalam Mendukung OMSP - Batubara, Zuhdi (Dinasti Research, 2024)
This research aims to analyze the enhancement of the Indonesian National Police Mobile Brigade Corps (Korps Brimob Polri) in handling terrorism threats involving Chemical, Biological, Radiological, and Nuclear (CBRN) materials, to support the implementation of Military Operations Other Than War (MOOTW). CBRN-based terrorism has become a serious threat in Indonesia and internationally, with increasing attacks using these dangerous materials from 2011 to 2019. Korbrimob, as the elite unit of the Indonesian National Police (Polri), plays a strategic role in addressing these threats. However, further development is needed in organizational capacity, human resources, equipment, and inter-agency coordination to improve handling effectiveness. This research employs a qualitative approach using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to evaluate the internal and external factors that influence Korbrimob’s capability in dealing with CBRN terrorism. Data was collected through interviews with stakeholders, document analysis, and field observations. Data validation was performed through triangulation techniques to ensure the accuracy of the research findings. The key findings of this study indicate that while Korbrimob Polri has established specialized CBRN units across Indonesia, several weaknesses persist, including equipment limitations, lack of adequate training, and ineffective synergy with relevant agencies, including the Indonesian National Armed Forces (TNI) and the National Counterterrorism Agency (BNPT). Korbrimob’s main strength lies in its personnel capabilities and cross-sectoral cooperation, but weaknesses in authority and resources hinder the necessary capacity improvements. This research recommends increasing Korbrimob’s authority in handling CBRN, developing specialized equipment, and enhancing joint training frequency with TNI and other relevant agencies to improve readiness in facing CBRN-based terrorism threats.